Effectiveness of Breast Cancer Awareness Month (BCAM) Before and After the COVID-19 Pandemic: Google Trends Analysis - Majed Ramadan; Walaa Alshekhi; Doaa Aboalola; Siham Aouabdi; Haneen Alzahrani; Abrar Ashi; Rawiah Alsiary (National Journal of Community Medicine)
Background: Breast cancer awareness month (BCAM) strategy has been established in Saudi Arabia to promote national knowledge about Breast Cancer, as the Saudi Cancer Registry annual reports reported that breast cancer has ranked first among other cancerous diseases in women. Early detection and the treatment in the early stages of the disease will increase the survival rate of breast cancer patients. Many detection techniques have been used for breast cancer. The objectives of this study are to investigate the popular pattern in seeking screening information of breast cancer in Saudi Arabia using Google Trends.